Piezoelectric and ferroelectric properties of lead-free Bi0.5(Na0.80K0.20)0.5TiO3-(Ba0.98Nd0.20)TiO3 binary system - Wannasut P. (2017)
© 2017 Taylor & Francis Group, LLC. This research was conducted to investigate the effect of (Ba 0.98 Nd 0.20 )TiO 3 addition on properties of Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 ceramic. The binary system having composition of(1-x)Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 -x(Ba 0.98 Nd 0.20 )TiO 3 or (1-x)BNKT-xBNdT (x = 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06 mol fraction) was prepared by a conventional mixed oxide and sintering method. From the characterization results, the ceramics sintered at 1125°C had relative density of more than 98% of their theoretical values regardless of BNdT content. X-ray diffraction pattern of the ceramics showed a single perovskite structure with mixed rhombohedral and tetragonal phases (i.e. within MPB region). Scanning electron micrographs showed a cubic-like grain shape and the grain size decreased with increasing BNdT content. The ceramic with x = 0.04 showed relatively high room temperature dielectric constant with low loss (ϵ r = 1670, tanδ = 0.0532), high piezoelectric coefficient (d 33 = 192 pC/N) and good ferroelectric properties (P r = 19.12 µC/cm 2 , E c = 13.54 kV/cm and R sq = 1.52) which may be suitable for transducer and actuator applications.